Law No. 215 of the year 2017 Amending Certain Provisions of Law No. 10 of the Year 2004 on Establishing the Family Courts = قانون رقم 215 لسنة 2017 بتعديل بعض أحكام القانون رقم 10 لسنة 2004 فى شأن إنشاء محاكم الأسرة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic